Numerical simulation of GTAW for ZW61 magnesium alloy thin plates: Coupling the finite element method with the cellular automata method - Qichi Le; Weiyang Zhou; Qiyu Liao; Dazhi Zhao; Ye Shi (Journal of Materials Research and Technology)
ZW61 magnesium alloy has a wide range of application prospects as a lightweight green engineering material. In this paper, the temperature field and microstructure of gas tungsten arc welding (GTAW) for ZW61 magnesium alloy are simulated by the finite element method and the cellular automata (CA) method. The results show that the microstructure in the center of the fusion zone (FZ) is all equiaxed grains affected by compositional supercooling. While at the edge of the molten pool, the crystals produced by associative crystallization evolve into columnar grains after undergoing competitive growth. Furthermore, the temperature field of the molten pool alters as the welding heat input increases. Especially, the temperature gradient behind the molten pool slows down. Thus, the cooling rate during solidification of the molten pool decreases, increasing the size of the weld microstructure. Meanwhile, solute concentration plays an essential role in the weld microstructure evolution. The rise in Zn content both refines the size of the equiaxed grains and inhibits the growth of the columnar crystals. Moreover, the experimental results of the thermal cycling curves and the FZ microstructure exhibit minimal error with the simulation results, verifying the reliability of the model.